Holy Hills of the Ozarks Religion and Tourism in Branson, Missouri - Ketchell, Aaron K. (Johns Hopkins University Press, 2007)
Over the past century, Branson, Missouri, has attracted tens of millions of tourists. Nestled in the heart of the Ozark Mountains, it offers a rare and refreshing combination of natural beauty and family-friendly recreation-from scenic lakes and rolling hills to theme parks and variety shows. It has boasted of big name celebrities, like Wayne Newton, Andy Williams, and Petula Clark, as well as family entertainers like Mickey Gilley, the Shanghai Magic Troupe, Jim Stafford, and Yakov Smirnoff.But there is more to Branson's fame than just recreation. As Aaron K. Ketchell discovers, a popular variant of Christianity underscores all Branson's tourist attractions and fortifies every consumer success. In this lively and engaging study, Ketchell explores Branson's unique blend of religion and recreation. He explains how the city became a mecca of conservative Christianity-a place for a "spiritual vacation"-and how, through conscious effort, its residents and businesses continuously reinforce its inextricable connection with the divine. Ketchell combines the study of lived religion, popular culture, evangelicalism, and contemporary American history to present an accurate and honest account of a distinctly American phenomenon.